Dynamism of Monetary Transmission Mechanism in Nigeria: Interest Rate and Market Capitalization Causality Evidence - Agundu, Prince Umor C.; Henry Akani, Waleru (International Journal of Accounting & Finance Review, 2018)
The potency of monetary transmission channels anchors the process by which interest rate movements and other cardinal aggregates influence critical financial fundamentals in an economy. This study, thus, examines dynamism of the monetary transmission mechanism with focus on the causality of interest rate and market capitalization in the Nigerian economy. Time series data covering a period of 36 years (1981 - 2015) were extracted from publications of monetary authorities and related agencies, including annual reports of Deposit Money Banks (DMBs) in the country. Facilitated by E-Views software, the analytical proceedings generated the required statistical outcomes in terms of coefficient of correlation (r), coefficient of determination (R2), t-statistic, and F-statistic. Granger causality test was also conducted to clearly establish the direction of causality between the focal variables. Essentially, the null hypothesis is rejected as probability of the F-statistic is less than the specified 0.05 level of significance. The granger causality test statistics run from four interest rate components to the operational capital market fundamental (with F-statistics of 5.758, 5.540, 4.209,and5.656; as well as  probability values of 0.008, 0.009, 0.002, and 0.009 respectively). In view of the analytical outcomes, it is recommended that interest rate components be efficiently synergized to boost investors’ confidence and further drive monetary policy dynamics towards greater financial system vitality and sustainability in Nigeria.